PERCEPTION OF COLLEGE OF EDUCATION LECTURERS ABOUT TECHNICAL EDUCATION RESEARCH AND EVALUATION IN NIGERIA - Kennedy, O. O. (Sokoto Educational Review, 2013)
The study was conducted to ascertain the perception of Federal College of Education Technical lecturers towards technical education research in the South-South geo-political zone of Nigeria. In pursuance of this purpose, four research questions were formulated and one hypothesis tested. The population comprised of 70 lecturers of Federal Colleges of Education (Technical) in Asaba, Umunze and Omoku. The entire population was used for the study. No sampling was done because of the fewness of the population. The design used was a survey. The instrument used was the questionnaire. On the whole 57 items were drawn using the Likert scale format. The instrument was considered valid by experts with the reliability coefficient of 0.89 using Cronbach alpha. Simple percentage and t-test were used to analyse the data. The study revealed that: Government’s inactive role in supporting and promoting research activities in colleges of education (technical) caused low morale of lecturers towards research; A lot of constraints such as poor attitude to research, falsification of research data, among others are the challenges of technical education research. The study recommends among others that: About 10 per cent of the education tax fund should be voted to research; Government should improve its communication network.